MODERN VIEW ON THE PROBLEM OF ANTIBIOTIC RESISTANCE IN PULMONOLOGY AND PHTHISIATRY (LITERATURE REVIEW) - Pylypiv, Lesya; Piskur, Zoriana (Eastern Ukrainian Medical Journal, 2024)
Introduction. The problem of antibiotic resistance (AR) is threatening for patients with respiratory tract diseases (RTD). The use of antibiotics in the treatment of pneumonia, which can be prescribed in the schemes for the tuberculosis (TB) treatment, creates the prerequisites for the formation of chemoresistance (CR) of mycobacterium tuberculosis (MBT).The purpose of our research is to analyze the scientific literature on the causes and factors of the occurrence of AR of the сommon RTD pathogens (pneumonia, tuberculosis).Materials and methods. The information on AR of pneumonia and tuberculosis causative agents obtained from scientific publications published in the «pubmed» and «scopus» databases has been analyzed.Results. The main factors causing AR in European countries today are: low awareness of the public and medical professionals about AR, over-the-counter purchase of antibiotics, use of antibiotic residues, the desire of doctors to avoid complications of the disease, advertising of pharmaceutical products, frequent lack of diagnostic tests to detect common infections. The vast majority of antibiotic prescriptions in ambulatory practice are for the treatment of respiratory tract infections, but up to 90% of them are unwarranted.Сoncomitant diseases of the patient (chronic kidney disease, bronchopulmonary diseases, liver diseases), previous colonization of the oropharynx with AR pathogens, bedridden state, age up to 2 years can be risk factors for AR of pneumonia pathogens. The physician should be alert for M. tuberculosis infection and perform appropriate diagnosis in patients with suspected pneumonia, especially in children, the elderly, and patients with HIV and comorbidities.It has been established that less than 65 years of age, living in a large family, history of TB treatment, contact with TB patients, history of hospitalization and visits to medical institutions, TB/HIV co‑infection, bad habits (smoking, alcohol consumption), glycosylated hemoglobin level ˃ 7% were risk factors for chemoresistant TB in adults. Risk factors for chemoresistant extrapulmonary TB in children were: up to 1 year of age, living in a village, poor family income, contact with bacterial isolates of resistant MBT strains, lack of BCG vaccination, concomitant pathology.Conclusions. In order to reduce the prevalence of AR of the RTD pathogens, clear algorithms for prescribing antibiotics should be developed, patients should be trained in their correct use, and methods of diagnosing common infections should be improved. In order to overcome CR TB, it is necessary to detect patients in time and block the transmission of infection, develop clear control algorithms for the detection and treatment of CR TB in risk groups, for example, among patients with diabetes, intensify the development of drugs with new mechanisms of action, initiate testing for the detection of TB in risk groups with suspected pneumonia.